The Critical Study of Goethe’s Muhammad Drama for Exploring Its Spark of Creation and The Reasons of Incompletion - Shahryar, Ali; Hang, Nguyen Thi (Indonesian Center for Religion and Society Studies (InTReSt), 2025)
Goethe, through orientalism, became familiar with the character of the Prophet Muhammad (PBUH), then in 1773 he decided to write a Drama with the title of “Muhammad Drama.” After the completion of a few parts, he left it incomplete. Therefore, the present research has been conducted based on a mixed research framework of intellectual-historical and genetic criticism to critically study the remaining fragments of drama and discover the inspiration for creation and the reasons for the incompletion of the mentioned work. The close study of the mentioned topic suggests that the optimal character of the prophet, whose eager soul long been searching, inspired him to initiate this work, yet, due to his teacher’s advice and other crucial societal considerations, he left it incomplete. The literary metaphors in remained fragments for prophet companions and the influence of the character of prophet Muhammad as a role model in other works of Goethe need to be explored.